2003
DOI: 10.1637/0005-2086(2003)047[0476:ivsoor]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Ornithobacterium rhinotracheale to Several Antimicrobial Drugs

Abstract: As part of the basic characterization of Ornithobacterium rhinotracheale, the minimal inhibitory concentrations of 10 antimicrobial drugs were determined for reference strains and Mexican isolates by a broth microdilution method. For optimal growth of the organisms, a supplemented brain-heart infusion broth was used. The susceptibility of O. rhinotracheale to amoxicillin, enrofloxacin, and oxytetracycline was variable. However, consistent higher minimal inhibitory concentrations values were obtained for gentam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 14 publications
3
15
0
2
Order By: Relevance
“…At the same time, most authors found O. rhinotracheale strains to be resistant to gentamicin (Ak and Turan, 2001;Malik et al, 2003a;Soriano et al, 2003;Murthy et al, 2008) and sulphamethoxazole-trimethoprim (Malik et al, 2003a;Tsai and Huang, 2006;Mohd-Zain et al, 2008;Murthy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, most authors found O. rhinotracheale strains to be resistant to gentamicin (Ak and Turan, 2001;Malik et al, 2003a;Soriano et al, 2003;Murthy et al, 2008) and sulphamethoxazole-trimethoprim (Malik et al, 2003a;Tsai and Huang, 2006;Mohd-Zain et al, 2008;Murthy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Varga et al (2001) observed low MICs to erythromycin; however, the drug inhibited the growth of O. rhinotracheale strains only in high concentrations or not at all in the Netherlands (van Veen et al, 2001). Similarly, the susceptibility of Mexican strains to amoxicillin ranged from 16 µg/ml to 128 µg/ml with only one susceptible isolate at 2 µg/ml (Soriano et al, 2003), and all Dutch isolates were resistant, too (64 µg/ml) (van Veen et al, 2001) whereas elsewhere a wider range (≤ 0.06 µg/ml to ≥ 64 µg/ml) was reported (Varga et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, pairs of O. rhinotracheale isolates (stable O. rhinotracheale SCVs and their WT counterparts) that showed different patterns of susceptibility to certain antibiotics were further tested to identify the MIC values for those antibiotics, as described previously (36). Therefore, O. rhinotracheale isolates were grown on TSB supplemented with 5% FBS and 2% IsoVitaleX Enrichment at 37°C under microaerobic conditions (see below), and standard microdilution procedures were conducted using the same medium and conditions to determine MIC values.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, other infectious agents of the respiratory tract such as Escherichia coli (24), Bordetella avium (7), and Newcastle diseases (ND) virus (31) have a triggering effect on the manifestation of O. rhinotracheale infection. Treatment of O. rhinotracheale infection is becoming more and more difficult, as most isolates have acquired resistance against the regularly used antibiotics (8,17,29). Therefore, administration of a suitable vaccine inducing protective immunity against O. rhinotracheale infection is a good solution.…”
mentioning
confidence: 99%